Hair Regrowth in Alopecia Areata Patients: Insights from a Case Study Using Mesenchymal Stem Cell Conditioned Media - Mahmood, Anjum; Seetharaman, Rajasekar; Kshatriya, Prashant; Patel, Divyang; Mishra, Rangnath; Srivastava, Anand S (Medicine and Medical Research: New Perspectives Vol. 12, 2024)
The present study investigated the therapeutic effects of MSC-derived Conditioned Media (CM), on a patient with alopecia areata, and results reported here were inferred on an observational basis. Hair follicle transplant demands and, therefore, is carried out using advanced surgical procedures involving the implantation of hair follicles in the afflicted regions. Alopecia Areata (AA), an indication characterized by hair loss patches in the scalp region, caused primarily by an autoimmune disorder, affects a significant fraction of the population globally. The disease hampers quality of life causing anxiety and low self-esteem in patients. This case report discusses the condition of an alopecia areata patient and her subsequent treatment with Mesenchymal Stem Cell-derived Conditioned Media (MSC-CM). The severity of the disease was assessed by calculating the Severity of Alopecia Tool (SALT) score which was 6%. The topical treatment for two months resulted in visible hair growth in the vertex scalp area with a SALT score approaching 0%. The functional roles of MSCs are mostly facilitated by a number of secreted cytokines and growth factors. In the case discussed here, adipose-derived MSCs were used to generate conditioned media (MSC-CM) consisting of secretory molecules. In the surrounding medium, MSCs produce a variety of growth factors, cytokines, lipid vesicles, and paracrine chemicals that may control hair follicle growth, vascularization, and morphogenesis. According to this study, applying topical MSC-CM therapy can improve alopecia and encourage the creation of new hair. Exosomes and paracrine factors may passively diffuse to mediate this.